Alcalde, Arturo, Graciela Bensusán (coord.) Enrique de la Garza, Enrique Hernández Laos, Teresa Rendón (coord) y Carlos Salas. Trabajo y trabajadores en el México contemporáneo. México, D.F. : Miguel Ángel Porrúa, 2000 - García, Brígida (Estudios Demográficos y Urbanos, 2001)
Alcalde, Arturo, Graciela Bensusán (coord.), Enrique de la Garza, Enrique Hernández Laos, Teresa Rendón (coord.) y Carlos Salas, Trabajo y trabajadores en el México contemporáneo, México, Miguel Ángel Porrúa, 2000.